معالم الجماعة الدعوية الفعالةفي ضوء أحوال العمران البشري وسننه عند ابن خلدون = ma'alim al-jama'at al-da'awiyyah al-fa'alah fi du'i ahwal al-umran al-basyar wa sunanuhu 'inda ibn khaldun (Indicators of efficient missionary community in light of the conditions and laws of human civilization according to Ibn Khaldun / Penunjuk kumpulan da'wah efekttif berdasarkan ehwal dan tata tamadun manusia menurut Ibn Khaldun) - Salah, Machouche (International Islamic University Press, 2012)
The article looks into the psychological and social factors shaping the success and prosperity of missionary or da'wah groups (al-jamii'ah al-da 'awiyah) in accordance with the conditions of human civilization (al' umran al-bashari). This has been done by higlighting Ibn Khaldun's (d. 808 AH/l406 AD) view of human association and his identification of the dimensions and psychological, cognitive, social and cultural conditions of missionary or da'wah activities. For this the author has analyzed a set of factors that are necessary for the edifying and management of efficient and efficacious da'wah groups, while highlighting the correlation among those factors. The author also attempted to identify a set of criteria that are required for explaining and measuring the quality of efficiency and efficacy as pertains to da'wah groups seen in the religious and faith context of such groups. The develop his thesis and support his conclusions, the writer has undertaken a thematic reading of the fundamental textual sources of Revelation and analysis of Ibn Khaldun's discourse in the Muqaddimah as regards the nature, shaping and definition of efficacious da'wah group. He also drew on the works of a considerable number of contemporary scholars and researchers who addressed many issues concerning the methods and goals of da'wah as well as the challenges facing it. All this has been done while due attention is paid to the generation religious situation engulfing Muslim society at the present.